MANAGERS MENTAL ACTIVITY IN THE LIGHT OF CYBERNETIC EPISTEMOLOGY (COMPLEXITY THEORY) - S. Kretov (Управленческие науки, 2016)
All the processes in the humane community are managed without exception. The society like all other complex systems is subdivided into managing and managed sub-systems. Currently the working out of managerial decisions is exercised with the account of many factors, but the most important process,e. the transformation of “the territory into a map” is located beyond the borders of managers’ awareness. The methodology of cybernetic epistemology (complexity theory) has allowed the author to formulate the substantial explanatory paradigm of this managerial activity’s ignored factor.